2021
DOI: 10.17352/jvi.000041
|View full text |Cite
|
Sign up to set email alerts
|

Convenience and economic benefit of early one-shot Mycoplasma hyopneumoniae vaccination at 3 days of age in a commercial sow farm

Abstract: Mycoplasma hyopneumoniae (M. hyopneumoniae) is the primary pathogen of enzootic pneumonia, a chronic respiratory disease in pigs. Vaccination of piglets to protect against M. hyopneumoniae can be performed at several ages, depending on product label specifi cations. Early intervention in the fi rst week of life may have advantages, since piglets can already become infected with M. hyopneumoniae during the suckling period, resulting in a signifi cant percentage of M. hyopneumoniaepositive piglets around weaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Their findings revealed that a three-dose regimen of commercial bacterin vaccination vitally abolished lung lesions at 28 days post-infection in tested gilts, along with an overall decrease in bacterial load in vaccinated gilts. In another study focusing on the practicality and monetary advantages of immunizing piglets against the bacteria at different ages, it was established that immunization at three days of age conferred a substantial advantage over-vaccination at 7 or 14 days of age (Vangroenweghe, 2021).…”
Section: Economic Impactmentioning
confidence: 99%
“…Their findings revealed that a three-dose regimen of commercial bacterin vaccination vitally abolished lung lesions at 28 days post-infection in tested gilts, along with an overall decrease in bacterial load in vaccinated gilts. In another study focusing on the practicality and monetary advantages of immunizing piglets against the bacteria at different ages, it was established that immunization at three days of age conferred a substantial advantage over-vaccination at 7 or 14 days of age (Vangroenweghe, 2021).…”
Section: Economic Impactmentioning
confidence: 99%